DKK3 initially preserves acinar integrity through MEK-Fos signaling, but later switches to an oncogenic role in pancreatic cancer - Srinivasan, Dharini; Roger, Elodie; Perkhofer, Lukas; Zimmer, Eleni; Barth, Thomas F.E.; Mosler, Julia P.; Härle, Anna; Weissinger, Stephanie E.; Gaisa, Nadine T.; Möller, Peter; Fischer, Nico; Allgöwer, Chantal; et al. (Advanced science, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by its intricate biology governed by spatiotemporal dynamics in the expression and function of specific proteins. Here, DKK3 is identified as a dynamic player with a dual role in PDAC. Using the KRASG12D-driven mouse model with homozygous (DDKC) and heterozygous (DKC) DKK3 knockout, its stage and compartment-specific functions are investigated. Knockout mice exhibited shorter lifespans with a higher incidence of high-grade, desmoplastic, and metastatic cancers. DKK3-deficient acini exhibited a marked increase in acinar-to-ductal metaplasia, with increased MAPK signaling and induction of the downstream effector Fos. During the progression of mouse and human PDAC, DKK3 expression shifted from epithelial dysplastic cells to cancer-associated fibroblasts (CAFs). At the endpoint, DKK3-expressing CAFs emerged as crucial contributors to tumor aggressiveness and fibrosis. Orthotopic transplantations confirm a stromal role, particularly in DDKC tumors, while mechanistic studies demonstrate that DKK3 activates IL6-JAK-STAT3 signaling and pro-migratory/mesenchymal programs that are reversed by pharmacologic STAT3 inhibition in DDKC cells. Concordantly, DKK3 expression correlates with IL6-JAK-STAT3 gene signatures in human PDAC datasets. Together, these findings underscore the intricate and context-sensitive role of DKK3, delaying oncogenesis during early stages while paradoxically promoting tumor progression in later stages, suggesting that therapeutic targeting strategies should be approached with caution.
Gesehen am 09.12.2025